Circulating and adipose tissue matrix metalloproteinases in cardiometabolic risk environments: pathophysiological aspects - Berg, Gabriela Alicia (2014)
Matrix metalloproteinases (MMPs) play an important role during physiological tissue remodeling in embryonic development and angiogenesis, as well as in pathophysiological conditions such as obesity and development and vulnerability of atherosclerotic plaque. Moreover, MMP circulating levels have emerged as potential biomarkers of cardiovascular disease. MMP expression and activity are regulated by different factors such as insulin resistance and obesity. Expanded fat tissue has been demonstrated to be an active organ, where MMPs also exert a role in adipogenesis, angiogenesis, and proliferation of extracellular matrix (ECM). However, the lack of association between adipose tissue and plasma levels of some MMPs, specifically MMP-2 and MMP-9, suggests that this tissue is not a major contributor to circulating gelatinases. MMPs are also co-expressed or co-repressed in response to inflammatory adipocytokines, like adiponectin and leptin. Adiponectin may also play a protective role in plaque rupture through selectively increasing the tissue inhibitor of metalloproteinase (TIMP) expression. Leptin induces the expression of MMP-2 activators as well as the expression of MMP-2, MMP-9, and TIMP-1 in different human cells. Furthermore, sex hormones also participate in MMP regulation. In postmenopausal women, hormone replacement therapy produces an increase in MMP activity, leading to a breakdown in ECM homeostasis and accelerated progression of vascular pathologies. Besides, in men, an inverse relationship between testosterone levels and MMP-2 activity has been described. It is still necessary to go forward in the study of MMPs in different metabolic situations to corroborate their role as vulnerable plaque biomarkers.